Analysis of Logistics Planning in Puskesmas: An Approach to Operational Efficiency and Effectiveness - Rapotan Hasisbuan; Adinda Aulia Ar-ramdhani; Anggina Cucu Khetri Sianturi; Amelia Apriyuni; Dian Yustika Putri; Halimatus Sa'diyah Dalimunthe; Azzahra Ramadhana Nasution; Salsabila Audina (Universitas Muhammadiyah Palu, 2025)
This research aims to analyze logistics planning at community health centers with a focus on the methods used to determine logistics needs, monitor stock of goods, as well as procedures for handling sudden requests and writing off goods. This research uses a qualitative descriptive approach with in-depth interviews and observation methods at several community health centers in Medan City. The research results show that logistics planning at community health centers is carried out using a standard format provided by the Health Service every year, which includes estimates of drug needs based on previous usage data and disease patterns. The stoc monitoring process for logistics goods is carried out periodically with drug usage reports (LPLPO) which record stock, remaining stock and expenditure. Handling sudden requests is done by making special requests to the warehouse, although sometimes drug procurement cannot be fulfilled on time. The main challenges in logistics planning are budget limitations and ineffective coordination with related parties. Removal of expired or damaged goods is carried out using a procedure that includes separating the goods and making an official report. This research provides recommendations for improving coordination between parties, using technology in stock monitoring, and more efficient budget management so that logistics planning at community health centers can be more effective and support optimal health services.